(untitled) (Texas Journal of Medical Science, 2025)
This topic provides brief information about the anatomical and morphological structure of the heart, its chambers – the right and left atria and ventricles, the valve system, the role of the heart in blood circulation, and the layers of the heart wall (endocardium, myocardium, epicardium). It also covers the internal and external structures of the heart, the flow of blood through the heart, and the working principle of cardiac muscles. This topic is important for understanding the basics of heart function.